2017
DOI: 10.1007/s10570-017-1444-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the degree of substitution on the rheology of sodium carboxymethylcellulose solutions in propylene glycol/water mixtures

Abstract: The linear dynamic viscoelastic properties and non-linear transient rheology of sodium carboxymethylcellulose solutions (Na-CMC) in propylene glycol/water mixtures were investigated. Measurements were carried out for the solutions of Na-CMC with three different degrees of substitution (DS), namely 0.62, 0.79, 1.04, and the similar average molecular weight (M w & 250,000 g/mol). The strong synergism between the molecules of Na-CMC with DS of 0.62 and 0.79, and propylene glycol has been observed. The occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 44 publications
3
26
0
4
Order By: Relevance
“…SAOS measurement results for sodium carboxymethylcellulose solutions in PG/water mixture with a PG concentration of c PG ≥ 70% were discussed by Komorowska et al . The authors showed that the Na‐CMC 0.62 and Na‐CMC 0.79 chains undergo physical crosslinking, probably as a result of the formation of hydrogen bonds between OH groups of propylene glycol and Na‐CMC.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…SAOS measurement results for sodium carboxymethylcellulose solutions in PG/water mixture with a PG concentration of c PG ≥ 70% were discussed by Komorowska et al . The authors showed that the Na‐CMC 0.62 and Na‐CMC 0.79 chains undergo physical crosslinking, probably as a result of the formation of hydrogen bonds between OH groups of propylene glycol and Na‐CMC.…”
Section: Resultsmentioning
confidence: 99%
“…For Na‐CMC 0.62 and Na‐CMC 0.79 solutions, zero shear viscosity measurements were carried out in the polymer concentration range from 0.01% to 1.4%. Above the concentration of 1.4%, there was a strong increase in viscosity, and zero shear viscosity determination was impossible …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations